2019
DOI: 10.7150/jca.32739
|View full text |Cite
|
Sign up to set email alerts
|

Tracking knowledge evolution, hotspots and future directions of emerging technologies in cancers research: a bibliometrics review

Abstract: Due to various environmental pollution issues, cancers have become the “first killer” of human beings in the 21st century and their control has become a global strategy of human health. The increasing development of emerging information technologies has provided opportunities for prevention, early detection, diagnosis, intervention, prognosis, nursing, and rehabilitation of cancers. In recent years, the literature associated with emerging technologies in cancer has grown rapidly, but few studies have used bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Popular journals and other trends in a research area during a certain period can be easily identified and can provide a reliable reference for researchers (69). Furthermore, core journals provide a significant amount of information, which is helpful, especially when searching for documents or submitting research achievements (70,71). Among the journals in which DETC-related articles were published, the Journal of Investigative Dermatology has published the most articles, while articles in the Journal of Immunology have obtained the most total citations, and Science ranks first by citations per article ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Popular journals and other trends in a research area during a certain period can be easily identified and can provide a reliable reference for researchers (69). Furthermore, core journals provide a significant amount of information, which is helpful, especially when searching for documents or submitting research achievements (70,71). Among the journals in which DETC-related articles were published, the Journal of Investigative Dermatology has published the most articles, while articles in the Journal of Immunology have obtained the most total citations, and Science ranks first by citations per article ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Popular journals and their research trends in a particular field provide researchers with reliable references. In addition, core journals provide researchers with faster search routes and can serve as an important publication guide (Zhuang et al, 2014 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that G-H studies related to various potential mechanisms involve multiple disciplines and categories and hence should be comprehensively analyzed to understand developments, determine research status, and highlight cutting-edge trends. Bibliometric reviews, a common research instrument for comprehensive analysis, have been used to explore and visualize scientific progress in many health-related fields recently, such as rural environment and health (Zhang et al 2019), childhood obesity (Gehanno et al 2019), nursing research (Dardas et al 2019), emerging technology in cancers (Wang et al 2019), and healthcare informatics (Gu et al 2017, Kokol et al 2018. To date, according to the search results of Web of Science (WoS) and Google Scholar, research on bibliometrics and visualization methods has not been used to dig deeper into and reveal the full panorama of, G-H research.…”
Section: Introductionmentioning
confidence: 99%